The best of both worlds: Combining lineage‐specific and universal bait sets in target‐enrichment hybridization reactions. (7th July 2021) - Hendriks, Kasper P.; Mandáková, Terezie; Hay, Nikolai M.; Ly, Elfy; Hooft van Huysduynen, Alex; Tamrakar, Rubin; Thomas, Shawn K.; Toro‐Núñez, Oscar; Pires, J. Chris; Nikolov, Lachezar A.; Koch, Marcus A.; Windham, Michael D.; et al.
Abstract : Premise: Researchers adopting target‐enrichment approaches often struggle with the decision of whether to use universal or lineage‐specific probe sets. To circumvent this quandary, we investigate the efficacy of a simultaneous enrichment by combining universal probes and lineage‐specific probes in a single hybridization reaction, to benefit from the qualities of both probe sets with little added cost or effort. Methods and Results: Using 26 Brassicaceae libraries and standard enrichment protocols, we compare results from three independent data sets. A large average fraction of reads mapping to the Angiosperms353 (24–31%) and Brassicaceae (35–59%) targets resulted in a sizable reconstruction of loci for each target set (x̄ ≥ 70%). Conclusions: High levels of enrichment and locus reconstruction for the two target sets demonstrate that the sampling of genomic regions can be easily extended through the combination of probe sets in single enrichment reactions. We hope that these findings will facilitate the production of expanded data sets that answer individual research questions and simultaneously allow wider applications by the research community as a whole.